2021
DOI: 10.1186/s40793-021-00391-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantitative microbiome profiling for environmental antibiotic resistance surveillance

Abstract: Background Understanding environmental microbiomes and antibiotic resistance (AR) is hindered by over reliance on relative abundance data from next-generation sequencing. Relative data limits our ability to quantify changes in microbiomes and resistomes over space and time because sequencing depth is not considered and makes data less suitable for Quantitative Microbial Risk Assessments (QMRA), critical in quantifying environmental AR exposure and transmission risks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Membrane filtration is a recommended method for examining the microbiological quality and safety of water, being 0.45 µm pore size filtering membranes recommended (Method 1103.1; EPA-821-R-10-002; ISO standards). Considering that water microbiota may include bacteria with smaller dimensions, numerous studies have used membranes with a pore size of 0.22 µm, mainly when disinfection processes, which may contract the bacterial cell, are being studied [10,16,33,34]. A previous study with groundwater, characterized by a high diversity of strictly environmental bacteria, showed that the numbers obtained with 0.1 and 0.2 µm pore size filters were similar, while 0.45 µm pore size polyethersulfone filters consistently led to lower bacterial counts, although within the same order of magnitude [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane filtration is a recommended method for examining the microbiological quality and safety of water, being 0.45 µm pore size filtering membranes recommended (Method 1103.1; EPA-821-R-10-002; ISO standards). Considering that water microbiota may include bacteria with smaller dimensions, numerous studies have used membranes with a pore size of 0.22 µm, mainly when disinfection processes, which may contract the bacterial cell, are being studied [10,16,33,34]. A previous study with groundwater, characterized by a high diversity of strictly environmental bacteria, showed that the numbers obtained with 0.1 and 0.2 µm pore size filters were similar, while 0.45 µm pore size polyethersulfone filters consistently led to lower bacterial counts, although within the same order of magnitude [5].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the 16S rRNA gene amplicon sequencing has been largely used to assess water microbial composition [7][8][9]. While 16S rRNA gene amplicon sequencing provides an overview of the bacterial community composition, expressing each taxon as a percentage corresponding to the relative abundance, a quantitative measure of some bacterial groups or functions may be required for specific purposes [10]. One of the most used methods for quantitative determinations is quantitative PCR (qPCR) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread of antibiotic-resistant pathogens and incidental emergencies has drawn public attention to the issue of antibiotic resistance. Between 2014 and 2016, more than one million people died due to antibiotic-resistant microbial strain infections, and the death toll is anticipated to rise in the future [ 7 ]. Bacteria have developed various resistance mechanisms to withstand antibiotic exposure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%